Students' anxiety: An examination of the perception of facial threat and perceived paternal and maternal parenting style - Mustapha, Roslinda; Shahadan, Md Azman; Abdul Wahab Khan, Rahmatullah Khan; Stephan, Ian; Archer, Marc (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2017)
Previous studies found that, young adolescents are very sensitive to the parental behaviours and attitudes directed towards them. This suggests that those who have a negative perception towards their parents might also have a negative emotion and perception towards another person's appearance. The study investigates the relationship between anxiety and threat perception and how it is related to perceived parenting style. A total of 105 school students age between 16 to 19 years old have been recruited to answer a set of questionnaire of parenting style and anxiety. They are also required to identify the facial expression to explore the threat perceptions by looking at images of facial expression in 2 and 3 dimensions. These images are able to be transformed into 5 levels of anger using the FaceGen Modeller 3.5. Results demonstrate that (a) anxiety is positively related to perceived father and mother authoritative parenting styles, but negatively related to perceived father and mother permissive parenting styles; (b) perceived threat from anger expression is significantly and uniquely related to perceived parenting styles; and (c) perceived threat from facial emotion, is positively correlated with trait anxiety and no correlation is found with state anxiety. Thus, angry faces are perceived as threatening among students, and play a significant role in students’ emotional well-being and students-teacher interaction.